ROLE OF MOTIVATION FOR UNIVERSITY LIBRARIANS; A CASE OF THREE PUBLIC UNIVERSITIES IN ZAMBIA - Yolam, Musonda (African Journal of Education and Practice, 2020)
Purpose: The purpose of this study was to investigate factors which affect motivation of librarians in three selected Universities in Zambia namely; Mulungushi University, Copperbelt University and Nkrumah University. The objectives of this study were to determine the extent to which librarians are motivated in their work, to find out factors that influence motivation among librarians in the selected university libraries in the Central and Copperbelt provinces of Zambia, to assess the impact of communication and staff development on staff motivation in the selected university libraries in the Central and Copperbelt provinces of Zambia and to propose measures aimed at contributing towards job motivation among librarians from the selected university libraries in the Central and Copperbelt province of Zambia. Methodology: The study was a survey by design targeting library staff such as sub-librarians, assistant librarians, senior library assistants as well as library assistants. A sample of 103 respondents was selected using purposive sampling. The survey combined qualitative and quantitative methods; qualitative data obtained from interviews using administered and self-administered questionnaires and interview technique results were analysed by coding and regrouping similar themes using constant comparative techniques. Quantitative data was collected and presented statistically in form of percentages and graphs. Findings: Study indicated various factors which can motivate librarians to do more work such as responsibilities including, good salary, promotion and work achievement. Unique Contributions to Theory Practice and Policy: The uniqueness of this research is that the findings will be used as reference by future researchers on this or related topics and this will help manager to put in place measures which will help motivate library staff. Hence this will lead to attainment of hard work among staff and delivery of quality services to clients.